Tugas Guru dalam Perspektif al-Qur`an Surat al-Jumu’ah Ayat 2 - Minal Muslimin; Afrizal. M (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study aims to find out lesson contained in surah al-Jumu’ah verse 2 and to explore the existence of the teachers’ responsibilities in surah al-Jumu’ah verse 2. This is a library research in which the research activities are carried out by collecting data from various literatures that include books in libraries, documents, and others. The findings of this study show that the teachers’ responsibilities are similar to the duties of the prophets and apostles. Therefore the best way to be used by a teacher is to model and imitate what had been taught by the Prophet to his students (friends) in guiding, directing, advising, with the main duty is to always teach the Quran to the students to make them calm down and soften their soul in accepting lessons, cleanse their souls from the misguided understanding of ‘aqidah and the despicable nature leading to fitrah, noble character and purity of heart, teach the contents of the Quran, hadith, and science (wisdom) universally.